Socialization of Arduino-Based Organic Waste Destruction Tool for Kitchen Waste Utilization in Karang Besuki - Dura, Justita; Islamiyah, Mufidatul; Wahyuni, Tri; Cahyaningtyas, Fadilla (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The community service aims to socialize the early process of organic waste into organic fertilizer for local plants in Karang Besuki residents, Malang city, Indonesia. This addresses the community's lack of knowledge about kitchen waste utilization, limited access to waste management technology, and the need to understand the environmental benefits of proper waste management. Method: The team conducted socialization and demonstration using a simple automatic counting tool, involving residents of Karang Besuki village, students, and the proposing team. Practical Applications: This initiative simplifies organic waste processing for residents, allowing the waste to be used as fertilizer, thus promoting a healthier community environment. Conclusion: The community service activities made it easier for residents to process organic waste into fertilizer, enhancing waste management practices and environmental awareness in Karang Besuki village, Malang city, Indonesia.